2015
DOI: 10.1063/1.4921451
|View full text |Cite
|
Sign up to set email alerts
|

Bright reddish-orange emission and good piezoelectric properties of Sm2O3-modified (K0.5Na0.5)NbO3-based lead-free piezoelectric ceramics

Abstract: Reddish orange-emitting 0.948(K0.5Na0.5)NbO3-0.052LiSbO3-xmol%Sm2O3 (KNN-5.2LS-xSm2O3) lead-free piezoelectric ceramics with good piezoelectric properties were fabricated in this study, and the photoluminescence and electrical properties of the ceramics were systematically studied. Results showed that Sm2O3 substitution into KNN-5.2LS induces a phase transition from the coexistence of orthorhombic and tetragonal phases to a pseudocubic phase and shifts the polymorphic phase transition (PPT) to below room tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…Raman spectrum measurement is helpful to acquire the information on the phase structure of KNN‐based ceramics, because NbO 6 octahedron vibrations are relatively sensitive to the change in the phase structure . Figure (a) presents the Raman spectra of KNLN:Er/ x Yb ceramics with different Yb contents at RT, where ν 5 and ν 1 bands are relatively strong in the internal vibration modes of NbO 6 octahedron.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raman spectrum measurement is helpful to acquire the information on the phase structure of KNN‐based ceramics, because NbO 6 octahedron vibrations are relatively sensitive to the change in the phase structure . Figure (a) presents the Raman spectra of KNLN:Er/ x Yb ceramics with different Yb contents at RT, where ν 5 and ν 1 bands are relatively strong in the internal vibration modes of NbO 6 octahedron.…”
Section: Resultsmentioning
confidence: 99%
“…These RE‐doped materials own a great potential for device applications in low‐voltage field emission display (FEDs), vacuum fluorescent display, optoelectronic devices, and so on . Especially, RE‐doped ferroelectrics have been intensively investigated because they present both excellent piezoelectric and PL properties, which makes them become the promising materials for optical amplifiers, zero‐loss electro‐optical elements, monolithic multifunction compact devices . Moreover, RE elements with small ionic radii could modify the ferroelectric properties by improving the spontaneous polarization .…”
Section: Introductionmentioning
confidence: 99%
“…The BaTiO 3 ‐based solid solutions perform excellent electromechanical properties, but the low Curie temperature ( T C = 120°C) limits their applications in the devices which will be used under extreme conditions . The KNN, a solid solution of ferroelectric KNbO 3 and anti‐ferroelectric NaNbO 3 in the ratio of 1:1 with an ABO 3 perovskite structure, has attracted much attention because of its high Curie temperature ( T C = 420°C) and the excellent piezoelectric coefficient ( d 33 ) comparable to values obtained for Pb(Zr,Ti)O 3 . However, its high piezoelectric coefficient resulted from the polymorphic phase transition at room temperature generally leads to poor temperature stability, which would restrict its applications.…”
Section: Introductionmentioning
confidence: 98%
“…It has been demonstrated that the ferroelectric materials doped with rare‐earth elements (lanthanide), showed an enhancement in ferroelectricity as well as highly efficient photoluminescence (PL), so it is hopeful to achieve multifunctional properties in ferroelectric thin films by doping rare‐earth ions. Zhou et al demonstrated that Pr 3+ ‐doped Na 0.5 Bi 0.5 TiO 3 thin films simultaneously showed strong red emission and optimal ferroelectricity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation